Microbiota and metabolic syndrome - Yüksel Altuntaş; Adnan Batman (KARE Publishing, 2017)
The role of gut bacteria in the pathogenesis and treatment of various diseases has been a focus of attention in the last 10 years. Prevalence of diabetes, obesity, and cardiovascular diseases continues to increase, in spite of technological developments and treatment alternatives. Microbial dysbiosis, described as the decrease of useful bacteria and the increase of harmful bacteria, has been associated with diabetes, obesity, atherosclerosis, and metabolic syndrome. In microbial dysbiosis, increase of harmful metabolites and changes to composition of bile acids occur via carbohydrate and protein fermentation. As a result, insulin resistance pathways are activated, which initiate the processes of obesity, diabetes, and atherosclerosis. Healthy diet recommendations, including prebiotic and probiotic foods and the use of probiotic agents, look promising for future treatment of metabolic syndrome and cardiovascular diseases.